An inquiry into the state of mind of W.F. Windham, Esq. of Fellbrigg Hall, Norfolk, before Samuel Warren, Esq., Q.C., and a special jury, upon the petition of General Windham C.B., etc., the uncle of the alleged lunatic, and other members of the family, at Her Majesty's Court of Exchequer, Westminster, commencing December 16, 1861 (Oliver)
Commission de lunatico inquirendo.